Solid support or secret dissent? A list experiment on preference falsification during the Russian war against Ukraine - Philipp Chapkovski; Max Schaub (Research & Politics, 2022)
Do individuals reveal their true preferences when asked for their support for an ongoing war? This research note presents the results of a list experiment implemented in the midst of the Russian invasion of Ukraine. Our experiment allows us to estimate the extent of preference falsification with regard to support for the war by comparing the experimental results with a direct question. Our data comes from an online sample of 3000 Russians. Results show high levels of support for the war and significant levels of preference falsification: when asked directly, 71% of respondents support the war, while this share drops to 61% when using the list experiment. Preference falsification is particularly pronounced among individuals using TV as a main source of news. Our results imply that war leaders can pursue peace without fearing a large popular backlash, but also show that high levels of support for war can be sustained even once the brutality of the war has become clear.
doi:10.7910/DVN/FIMJQ1
Keywords: 320; conflict; war; public opinion; preference falsification; list experiment; Russia; Ukraine